2021
DOI: 10.1183/16000617.0011-2021
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatoid arthritis-interstitial lung disease: manifestations and current concepts in pathogenesis and management

Abstract: Rheumatoid arthritis (RA) is a systemic inflammatory disorder, with the most common extra-articular manifestation of RA being lung involvement. While essentially any of the lung compartments can be affected and manifest as interstitial lung disease (ILD), pleural effusion, cricoarytenoiditis, constrictive or follicular bronchiolitis, bronchiectasis, pulmonary vasculitis, and pulmonary hypertension, RA-ILD is a leading cause of death in patients with RA and is associated with significant morbidity and mortality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
135
2
17

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(158 citation statements)
references
References 143 publications
4
135
2
17
Order By: Relevance
“…Disease-modifying anti-rheumatic drugs (DMARDs), such as corticosteroids, conventional DMARDs (e.g. MTX), biologic drugs and targeted synthetic DMARDs, may increase the risk of infection and drug-induced lung injury [ 3 ]. Joint surgery can result in ventilator-induced lung injury if performed under general anaesthesia and with a ventilator.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Disease-modifying anti-rheumatic drugs (DMARDs), such as corticosteroids, conventional DMARDs (e.g. MTX), biologic drugs and targeted synthetic DMARDs, may increase the risk of infection and drug-induced lung injury [ 3 ]. Joint surgery can result in ventilator-induced lung injury if performed under general anaesthesia and with a ventilator.…”
Section: Discussionmentioning
confidence: 99%
“…Rheumatoid arthritis (RA) is an inflammatory autoimmune disease that predominantly affects the joints [ 1 , 2 ]. Interstitial lung disease (ILD) is a frequent extra-articular manifestation in RA patients and is linked to morbidity and mortality [ 3 ]. According to recent research, although overall RA-related mortality has reduced, RA-ILD mortality has not, indicating that enhanced RA care may have resulted in better overall outcomes but has limited therapeutic effect for the RA-ILD subgroup [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interstitial lung disease is often associated with rheumatic diseases. Its early diagnosis and management are not only difficult, but also crucial, because it is associated with major morbidity and mortality and can be the first cause of death in ARDs (7)(8)(9)(10)(11)(12)(13). We, therefore, aimed to measure consensus between specialists who can be involved in its management: this is one of the very first studies to address consensus between pulmonologists, rheumatologists, and radiologists.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a recent international consensus statement proposed "interstitial pneumonia with autoimmune features" as a new definition for ILD underlined by systemic autoimmune condition and not classifiable as any definite CTD, emphasizing the relationship between ILD and autoimmune response (5,6). In patients with rheumatic diseases, ILD is difficult to diagnose at an early stage, and can be associated with major morbidity and mortality, or even be the leading cause of death (7)(8)(9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…This finding allowed concluding that anti-MCV antibodies titers may work as an indicator correlating the disease activity and patient outcome [ 170 ]. Also, an attempt was made to characterize the etiology of rheumatoid arthritis from lung level (NCT03832374), as it was found that diffuse interstitial pneumopathy and bronchial dysfunctions occur in one-third of RA patients, and that some subtypes of ACPAs are preferentially present in the lungs [ 171 ]. This study (NCT03832374), still ongoing, addresses a very important question regarding the subtype(s) of ACPAs with a preferential tropism for the lung, that might be responsible for the infection within parenchyma and pulmonary airways, and the overall increased morbidity and mortality among RA patients with lung co-morbidities.…”
Section: Diagnostic and Therapeutic Potential Of Citrullinationmentioning
confidence: 99%